Design of Constant Modulus Discrete Phase Radar Waveforms Subject to Multi-Spectral Constraints - Yang, Jing; Aubry, Augusto; De Maio, Antonio; Yu, Xianxiang; Cui, Guolong (IEEE signal processing letters, 2020)
This paper deals with constant modulus waveform design in spectrally dense environments assuming a discrete phase code alphabet. The goal is to optimize the radar detection performance while rigorously controlling the injected interference energy within each shared band and enforcing a similarity constraint to manage some relevant signal features. To tackle the resulting NP-hard optimization problem, an iterative procedure characterized by a polynomial computational complexity, is introduced leveraging the coordinate descent method. Numerical results are provided to show the effectiveness of the technique in terms of detection performance, spectral shape and autocorrelation features.